Sessile drop evaporation approach to detect starch adulteration in milk. (January 2023) - Ishwarya S, Padma; Dugyala, Venkateshwar Rao; Pradhan, Shantanu; Basavaraj, Madivala G.
Abstract: Milk adulteration is a major challenge faced by the dairy sector. Starch is a common milk adulterant with negative impact on consumer health. The major shortfalls in the present methods for detection and quantification of starch in milk are the higher limit of detection (LOD) and the need for additional chemical reagents. Hence, developing a chemical-free method with lower LOD for starch in milk is urgently required, especially in low- and middle-income countries. We propose a sessile drop evaporation -based approach to detect starch adulteration in milk. The influence of starch adulteration on the evaporative deposition patterns is studied using light microscopy as a function of dilution level (10–50%, v/v), starch type (potato and tapioca starches) and starch concentration (0.005–0.2%, w/v). The dried deposit patterns formed after drying drops of pristine and adulterated milk at 60 °C are dictated by the competing effects of outward capillary flow and inward Marangoni flows. Confocal Raman spectroscopy indicated the presence of fatty acids and other lipophilic constituents at the center, a combination of proteins and lipophilic constituents at the edge, and starch in regions close to the coffee stain, i.e., at the edge of the dried deposits. Higher level of water addition and lower level of starch adulteration resulted in the formation of coffee ring deposits with larger width. Surface profilometry indicated a decrease in the height of coffee-ring with increase in the concentration of both water and starch. The width and maximum height of edge deposits thus measured are proposed as the parameters to quantify starch concentration in milk. The proposed approach is effective in detecting starch concentration as low as 0.005% (w/v), as well as identifying the starch type, thereby facilitating facile, rapid, chemical-free, and in situ detection of starch adulteration in milk. Graphical abstract: Image 1 Highlights: Dried deposit pattern at the edge to detect starch adulteration in milk. Dried deposit patterns were dictated by the coffee ring effect and Marangoni flows. Starch aggregates were located next to the edge deposit comprising protein and fat. Width and height of edge deposits as parameters to quantify the starch in milk. Sessile drop evaporation approach can detect starch in milk as low as 0.005% (w/v).